1996
DOI: 10.1007/bf01271246
|View full text |Cite
|
Sign up to set email alerts
|

The motor performance test series in Parkinson's disease is influenced by depression

Abstract: The Motor Performance Test Series (MPTS) is widely used for treatment control in Parkinson's disease (PD). To elucidate the possible influence of depression on the fine motor skills in PD, 54 patients with idiopathic PD were investigated with the MPTS. 27 patients with major intensity of depression were compared to 27 age and motor disability matched patients with minor symptoms of depression, evaluated by the Zung depression scale. As determined by the subtest aiming, a significant lower ability for precise, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 16 publications
1
25
1
Order By: Relevance
“…We may conclude that the optimal cut-off scores for the BdI and Gds15 did not differ substantially for screening depression in the community or in patients with pd. In our study, the level of depression was not correlated with the intensity of motor symptoms or with the functional capacity as was previously reported by others 25,26 , and we did not find an association between the degree of depression and the duration of the disease. The lack of association between motor and affective symptoms in pd is considered to be clinical evidence that depression may be induced by distinct pathophysiological mechanisms than those responsible for the motor signs.…”
Section: Discussionsupporting
confidence: 75%
“…We may conclude that the optimal cut-off scores for the BdI and Gds15 did not differ substantially for screening depression in the community or in patients with pd. In our study, the level of depression was not correlated with the intensity of motor symptoms or with the functional capacity as was previously reported by others 25,26 , and we did not find an association between the degree of depression and the duration of the disease. The lack of association between motor and affective symptoms in pd is considered to be clinical evidence that depression may be induced by distinct pathophysiological mechanisms than those responsible for the motor signs.…”
Section: Discussionsupporting
confidence: 75%
“…Plugging measures repetitive complex hand movements -the subject is asked to transfer 25 pins (diameter: 2.5 mm, length: 5 cm), individually and as quickly as possible, from a rack into a series of appropriate holes (diameter: 2.8 mm) of a contact board. Estimated is the time interval between plugging in the first and the last pin [11,12]. Beck's Depression inventory [BDI, mean: 7.0 B 6.12 (SD), range: 0-26, n = 33] was used to score intensity of depression in parkinsonian subjects.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, some studies have demonstrated a stronger correlation between the relative changes in disability in individuals diagnosed over 1 year [Brown et al, 1988], correlation between disability and depression late in the course of PD , and correlation between disability and cognitive impairment Tandberg et al, 1997]. Depression in PD is also correlated with decreased motor performance [Kuhn et al, 1996] and treating depression may improve motor function .…”
Section: Etiology Of Depression In Pdmentioning
confidence: 86%
“…These depressive symptoms were shown to have a significant impact on measures of quality of life [Kuopio et al, 2000]. Other researchers have found a similar association between depression and activities of daily living (ADLs), cognitive function Stern et al, 1993], and motor symptoms [Kuhn et al, 1996] in patients with PD.…”
Section: Impact Of Depression In Pdmentioning
confidence: 91%